Literature as cultural ecology sustainable texts - Zapf, Hubert 1948- (Environmental cultures series, 2016)
"Drawing on the latest debates in ecocritical theory and sustainability studies, Literature as Cultural Ecology: Sustainable Texts outlines a new approach to the reading of literary texts. Hubert Zapf considers the ways in which literature operates as a form of cultural ecology, using language, imagination and critique to challenge and transform cultural narratives of humanity's relationship to nature. In this way, the book demonstrates the important role that literature plays in creating a more sustainable way of life. Applying this approach to works by writers such as Emily Dickinson, Edgar Allen Poe, Herman Melville, William Faulkner, Toni Morrison, Zakes Mda, and Amitav Ghosh, Literature as Cultural Ecology is an essential contribution to the contemporary environmental humanities."--Bloomsbury Publishing